A Semantic Analysis of Denotative and Connotative Meaning in the Song “Risk It All” by Bruno Mars - Nessa Tri Fanny Lumban Tobing; Bernieke Anggita Ristia Damanik (Yayasan Literasi Sains Indonesia, 2026)
This study explores the semantic facets of denotative and connotative meanings in Bruno Mars's “Risk It All for You,” centering on the pivotal phrase “risk it all” (repeated in the chorus: “I'd risk it all for you”). Using a qualitative descriptive method, it breaks down selected lyrics to show layered interpretations.“I'd risk it all for you” (Chorus): Denotative meaning: Literally, it declares a readiness to hazard everything—finances, safety, future—for the loved one, forming a narrative of bold commitment and sacrifice. Connotative meaning: Implies profound vulnerability and emotional gamble, evoking devotion's terror and thrill; the gambling metaphor symbolizes life's high-stakes bets on love, resonating with listeners' fears of loss. Hyperbole intensifies this, suggesting total surrender. Contextual enhancers: The upbeat yet urgent tone and repetitive structure amplify connotations of unwavering loyalty amid uncertainty. Other lines reinforce this: “Even if it breaks me in two” adds hyperbolic imagery of self-destruction, while “No regrets, no looking back” underscores irreversible risk. Findings confirm denotative layers provide a clear love story, but connotative ones—via metaphor, symbolism, and word choice—infuse emotional depth. Ultimately, “risk it all” exemplifies how such interplay boosts the song's relatability, highlighting semantic analysis for appreciating contemporary lyric,because if the contents of this template are deleted, the numbers will be sorted automatically. If you want to try deleting the contents of this template, please backup it first.